Influence of augmented reality technique on the accuracy of autotransplanted teeth in surgically created sockets - María Teresa Marhuenda Ramos; Ignacio Faus-Matoses; Álvaro Zubizarreta-Macho; Elena Riad Deglow; Ana Belén Lobo Galindo; Francesc Abella Sans; Alba Belanche Monterde; Vicente Faus Matoses (BMC, 2024)
Abstract Background The objective of the present study was to evaluate the reliability of an augmented reality drilling approach and a freehand drilling technique for the autotransplantation of single-rooted teeth. Materials and methods Forty samples were assigned to the following surgical techniques for drilling guidance of the artificial sockets: A. augmented reality technique (AR) (n = 20) and B. conventional free-hand technique (FT) (n = 20). Then, two models with 10 teeth each were submitted to a preoperative cone-beam computed tomography (CBCT) scan and a digital impression by a 3D intraoral scan. Afterwards, the autotrasplanted teeth were planned in a 3D dental implant planning software and transferred to the augmented reality device. Then, a postoperative CBCT scan was performed. Data sets from postoperative CBCT scans were aligned to the planning in the 3D implant planning software to analize the coronal, apical and angular deviations. Student's t-test and Mann-Whitney non-parametric statistical analysis were used to analyze the results. Results No statistically significant differences were shown at coronal (p = 0.123) and angular (p = 0.340) level; however, apical deviations between AR and FT study groups (p = 0.008) were statistically significant different. Conclusion The augmented reality appliance provides higher accuracy in the positioning of single-root autotransplanted teeth compared to the conventional free-hand technique.